ANALYSIS OF POSTURAL CONTROL OF YOUNG WOMEN DURING EXPOSURE TO SENSORY PERTURBATIONS (Fiep Bulletin - online, 2012)
The aim of this study was to analyze the influence of sensory disturbance on postural orthostatic balance of young women, based on the oscillation of the pressure center. Participated in this study five women, with mean age 27,4 ± 5,4 years, body weight 598.7 ± 146.7 N, and height 1.7 ± 0,13 m. Data collection was performed on a force platform under four conditions, with eyes open and eyes closed, with and without the foam backer. Three repetitions of 60 seconds for each condition. The variables analyzed were: RMS velocity average, and RMS displacement of the center of pressure. The results obtained showed that the foam support with increased body sway in both situations visuals, and yet, deprivation of vision also increased body sway in different situations of support.
Keywords: postural control; sensory disturbances; posturography.